Determination of Warming Modes for Seminiferous Tubules of Rat’s Testes After Vitrification - Volkova, Nataliia; Yukhta, Mariia; Sokil, Larisa; Chernyshenko, Lyudmyla; Stepaniuk, Lyudmyla; Goltsev, Anatoliy (Problems of Cryobiology and Cryomedicine, 2021)
Probl Cryobiol Cryomed 2021; 31(1): 095–099